(untitled) (Eurasian Journal of Ecology, 2019)
Abstract. One of the most widespread and dangerous diseases of wheat is the common bunt, which is caused by the fungi Tilletia caries (DC.). The most effective method of combating smut is considered to be genetic protection of plants, which is achieved by the introduction of new resistant samples to common bunt wheat. There is information about more than 15 genes that can express resistance to this disease. A number of molecular markers associated with the main genes of resistance to common bunt have been developed. They will be used to create common bunt resistant samples by screening and introgression of Bt-genes resistance into wheat samples with good economic value traits. The aim of the study is to identify carriers of resistance to common bunt using molecular markers. Molecular and phytopathological screening of Romanian wheat samples for resistance to common bunt Tilletia caries (DC.) was carried out. Molecular screening of Romanian samples for resistance to common bunt showed that 2 samples (02429GP-1, F08245G1) possess the Bt9 gene. When using a primer for PCR to the FSD / RSA locus, the Bt10 resistance gene was detected in two samples. As a result of phytopathological analysis, it was found that 5 samples (02429GP-1, F08126G1, F08245G1, F08347G1, F07270G2) are highly resistant to common bunt. Retezat showed a susceptible response with a lesion of 52%. The data obtained are valuable in breeding programs to increase resistance to common bunt. Key words: wheat, molecular screening, resistance genes, phytopathological assessment, common bunt.